Dietary Habits of Children 0-23 months in Rural Kansas: Early Life Diets of Rural Children - MacKenzie Gwinner; Arika Marchetti; Lynn Chollet-Hinton; Lynn Fisher (Kansas Journal of Medicine, 2023)
Introduction. Children in rural areas face increased rates of obesity compared to their urban counterparts, and diet in early childhood may influence the development of diseases related to food intake. This study sought to determine current diet of children 0-23 months of age in rural Kansas. Methods. Medical students participating in summer rural clinical experiences offered the survey to caregivers of children 0-23 months, born at term as singletons without a specialized diet. Recruitment occurred at appointments over 6 weeks in primary care offices. The survey was in the style of a validated Food Frequency Questionnaire for infants with an image for estimating portion sizes. Diets were compared to guidelines set by the Dietary Guidelines for Americans, 2020-2025. Results. Of 44 participants in the study, there were 21 children aged 0-5 months, 7 aged 6-11 months, and 16 aged 12-23 months. Breastfeeding rates were nearly double reported national averages. All children in the 0 to 5 month age group met guidelines. None of the children 6 to 11 months or 12 to 23 months met guidelines. In the 6 to 11 month group, 4 consumed food in addition to breastmilk or formula (complementary foods). In the 12-23 month group, protein and dairy foods were lower than, and whole grains and vegetables were higher than, reported national averages respectively. Conclusions. Children may fall short of dietary recommendations due to the amounts and types of food complementary to breast milk received in the diet.